An evidence-based approach to the post-marketing withdrawal of medicinal products because of adverse reactions - Onakpoya, I (2017)
Background: The aim of this thesis was to develop an evidence-based approach to the post-marketing withdrawal of medicinal products when harms are attributed to their use. Methods: Electronic and non-electronic searches were conducted to identify medicinal products withdrawn from the market because of adverse reactions. Data relating to the time periods between launch, first adverse reaction reports and withdrawals, the mechanism through which the adverse reactions occurred, and the countries of withdrawal were extracted. Standard criteria were used to document the levels of evidence used by drug regulators to make the withdrawal decisions; scatter plots and two-by-two tables used to explore the trends over time. A previously published algorithm was used to examine the justification for withdrawals. To examine the benefits and harms of medicinal products before regulatory approval, searches were conducted on drug regulatory websites and scientific databases. The Cochrane criterion was used to examine the risk of bias, Review Manager Software for meta-analysis, and GRADE criterion to rate the quality of evidence. Results: Improvements in pharmacovigilance over the past six decades have resulted in quicker detection of harms caused by approved medicinal products; however, there have not been corresponding improvements in how quickly harmful products are withdrawn from the market following the reports of harms. Harmful drugs are significantly less likely to be withdrawn in low resource settings. The quality of evidence in drug trials for which regulatory approval decisions are based is on the whole, poor. There is a lack of consistency in the methods used by drug regulators to assess the harms of medicinal products before granting marketing licences. Conclusions: Universally accepted guidelines for deciding when to withdraw approved medicinal products from the market should be developed. Pharmacovigilance systems in low-resource settings should be strengthened. The methods used to assess harms in clinical trials require improvement.